Variable Global Optimization min-sum (VGOMS) algorithm of decode-and forward-protocol for the relay node in the cooperative channel - Hushairi, Zen; Al-Khalid, Hj Othman; Khairuddin, Abdul Hamid; Jamaah, Suut (Springer, 2020)
The excessive delay due to the complexity of the decoding process at the relay node results in additional delays at the destination which is a signiﬁcant issue in cooperative communication channels. A low complexity min-sum (MS) based algorithm called the Variable Global Optimization min-sum (VGOMS) algorithm has been developed to minimise the error corrective performance. The proposed VGOMS algorithm apply the optimization scaling factor at the bit node processing of the variable node operation which have signiﬁcantly less complexity as compared with the check node operation or both variable node and check node operation. In this study, a straightforward Particle Swarm Optimization approach was used to determine the optimal scaling factor to obtain optimized error corrective performance of the algorithm. The proposed system model uses the channel combining large-scale and small-scale effects which used extensively in cooperative communications. The performance of the VGOMS algorithm performance was compared with four existing decoding algorithms (MS, OMS, NMS, SP) and was found better than the original min-sum (MS) in term of bit error rate (BER) performance and the ﬁrst algorithm reach optimal BER in error ﬂoor region from 3 others existing decoding algorithm (MS, OMS, NMS) after Sum-Product (SP) algorithm. The VGOMS algorithm was therefore shown to have a signiﬁcantly better compromise between the implementation of good error performance and low computational complexity.